2013
DOI: 10.1177/1938965513504483
|View full text |Cite
|
Sign up to set email alerts
|

Eco-friendly Attitudes, Barriers to Participation, and Differences in Behavior at Green Hotels

Abstract: A deeper understanding of customers’ desire for and participation in green activities can lead to organizations designing more efficient and effective green programs. This research finds that the guests’ assessment of the importance of being environmentally friendly has the greatest effect on their intention to stay in a green hotel. Second, the research identifies the following customer barriers to participation: inconvenience, perceptions of cost cutting, and decreased luxury—all of which significantly affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
188
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(197 citation statements)
references
References 32 publications
5
188
0
4
Order By: Relevance
“…Several studies found that individuals who already participated in general pro-environmental behaviour or consumption practices were more likely to choose to stay at a green hotel, over those who did not [67,76]. A consumer's "green" attitude is therefore a key mediator of their intention to stay at a green hotel [77].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies found that individuals who already participated in general pro-environmental behaviour or consumption practices were more likely to choose to stay at a green hotel, over those who did not [67,76]. A consumer's "green" attitude is therefore a key mediator of their intention to stay at a green hotel [77].…”
Section: Resultsmentioning
confidence: 99%
“…The most common sustainable hotel practices that customers appeared to value and think of were the use of recycle bins and recycled products, as well as reusable towel and linen schemes [39,47,63]. Inconvenience remains a powerful barrier to consumers in adopting sustainable practices in hotels [67].…”
Section: Resultsmentioning
confidence: 99%
“…manipulative intent) attributed to the application of green practices. The effects of perceived trade-offs of green lodging services on consumers' preferences is another relevant, evolving issue (Baker et al, 2014;Olson, 2013). Also, prior work has demonstrated that consumers may experience a higher level of sensitivity to justice when consuming luxury products (Kivetz & Simonson 2002).…”
Section: Current Issues In Tourismmentioning
confidence: 99%
“… In line with calls by various researchers such as Baker et al (2013), Millar and Baloglu (2011) and many more, studies examining hotel consumer behaviour should be undertaken in actual hotel settings to increase their validity. There is therefore a need for researchers to dialogue with hotel owners to allow researches to be carried out within their premises and with clients but in a winwin situation.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%